Uso de TIC y productividad en México: Un análisis subsectorial - Héctor Eduardo Díaz Rodríguez; Magnolia Miriam Sosa Castro; Alejandra Cabello Rosales (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
– Since Information and Communication Technologies adoption has grown, research on link of ICT and Economic Growth link has been rapidly developed, both in academic world and by governments and cooperation and development agencies. Research has found that there is a significant impact of the use of ICT on growth; however, it generally ignores the determinants of use. This is clearly visible in the case of studies carried out for the Mexican economy. This paper analyzes the determinants of differentiated use of ICT at subsector level in Mexico. using factor analysis, cluster analysis and econometrics, we find evidence related to the capacity (educational level and organizational maturity) that determines the use of ICT and, therefore, the strength of the impact of ICT on labor productivity in Mexico.
Keywords: J24; O47; D24; 330; subsector; ICT; labor productivity; factor analysis; cluster analysis; cross section